Rapid detection of circulating antigens and antibodies in experimental Trypanosoma evansi infection - SINGH, VEER (The Indian Journal of Animal Sciences, 2013)
Counter-current immunoelectrophoresis (CIE) and enzyme-linked immunosorbent assay (ELISA) were used for the detection of circulating antigens and antibodies in the serum of rabbits experimentally infected with Trypanosoma evansi. Antigen- detection tests became positive earlier than the antibody detection. ELISA could detect infection as early as 24-48 hr post-incoculation. Earliest positivity by Ab-ELISA was on the day 4 with a range of 4-6DPI, and by Ab-detection CIE on the day 5 with range of 5-8 days. No significant variations were onserved in the antigen and antibody detection between the experimental infections of rabbits by the 7.1 evansi stocks under study. The serological tests showed 3-4 times higher positivity than by the parasitological examination (WBE).